2021
DOI: 10.1080/10428194.2021.1964024
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib- and bortezomib-extended R-CHOP induction in elderly higher-risk patients newly diagnosed with diffuse large B-cell lymphoma – first analysis of toxicity and efficacy signals

Abstract: Ibrutinib-and bortezomib-extended R-CHOP induction in elderly higher-risk patients newly diagnosed with diffuse large B-cell lymphoma -first analysis of toxicity and efficacy signals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, preclinical trials suggested a synergistic effect of BTK inhibition and proteasome blockade, even in previously Bortezomib-insensitive cell lines [78]. Based on these considerations, ImbruVeRCHOP [49] is another actively recruiting early-phase clinical trial that investigates the combined BCR/NF-κB blockade by Ibrutinib and Bortezomib added to the R-CHOP backbone in elderly (age 61-80) patients with higher-risk disease (defined as IPI ≥ 2) but no pre-selection according to COO (see Table 1). Tolerated quite well in the context of a quadruple growth factor, antibiotics and antiviral prophylaxis have shown encouraging interim results [49,79].…”
Section: Targeted Therapies Addressing the Bcr/nf-κb Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preclinical trials suggested a synergistic effect of BTK inhibition and proteasome blockade, even in previously Bortezomib-insensitive cell lines [78]. Based on these considerations, ImbruVeRCHOP [49] is another actively recruiting early-phase clinical trial that investigates the combined BCR/NF-κB blockade by Ibrutinib and Bortezomib added to the R-CHOP backbone in elderly (age 61-80) patients with higher-risk disease (defined as IPI ≥ 2) but no pre-selection according to COO (see Table 1). Tolerated quite well in the context of a quadruple growth factor, antibiotics and antiviral prophylaxis have shown encouraging interim results [49,79].…”
Section: Targeted Therapies Addressing the Bcr/nf-κb Pathwaymentioning
confidence: 99%
“…Based on these considerations, ImbruVeRCHOP [49] is another actively recruiting early-phase clinical trial that investigates the combined BCR/NF-κB blockade by Ibrutinib and Bortezomib added to the R-CHOP backbone in elderly (age 61-80) patients with higher-risk disease (defined as IPI ≥ 2) but no pre-selection according to COO (see Table 1). Tolerated quite well in the context of a quadruple growth factor, antibiotics and antiviral prophylaxis have shown encouraging interim results [49,79]. A unique feature of this trial is its complex molecular program, seeking transcriptional profiles not only prior to first drug exposure, but directly under cycle 1 and, depending on the remaining lymphoma burden, further along in the course of therapy, with the declared aim of extracting a gene signature that indicates benefit from R-CHOP plus Ibrutinib and Bortezomib, potentially independent of a COO designation.…”
Section: Targeted Therapies Addressing the Bcr/nf-κb Pathwaymentioning
confidence: 99%